ANALYSIS OF EFFECTIVITY SCHEME BASED ON RISK MANAGEMENT AND EFFICIENCY FOR THE ACCELERATION OF CLEAN WATER FULFILLMENT IN INDONESIA - Wardhana, Yuki Mahardhito Adhitya (Journal of Environmental Science and Sustainable Development, 2020)
The Indonesian government has a target to provide 100% clean water through its “100-0-100 Urban” scheme. The objective is based on its Medium-Term Development Plan (RPJMN) 2015–2019 and the ambition to achieve the United Nations Sustainable Development Goals (SDGs) by 2030. The realization of a clean water supply, as of 2018, reached just 73%, and that in the cities, with only 2% growth per year. The cost needed to achieve the target of 100% clean water in Indonesia is Rp253 trillion. Given the fiscal limitations of the State Budget, financing alternatives need to be developed. Currently, there are two mechanisms to meet the needs of clean water in Indonesia, namely Public–Private Partnerships (PPP) and Conventional Government Procurement (CGP). The best scheme is the implementation of risk management and risk efficiency. This paper will analyze and compare CGP and PPP for their abilities to provide clean water with a risk efficiency approach, while still considering environmental sustainability and balance. The method that is currently being used to conduct this research is risk-based allocation method. The results of this study show that the PPP scheme is one of the most effective and sustainable, compared to others available in Indonesia. Via PPP, 43.8% of the allocated risk would be transferred from government risk to the project company, and some 25% would become shared risk. By this mode, it is predicted that using a PPP scheme could mitigate the risk of increased construction costs by approximately 71.6%, and 56.9% of the O&M cost. A PPP scheme for the water supply project in Indonesia is workable, bankable, and has the potential to finally fill in the water supply gap in Indonesia.